Is the BCG Vaccine Safe for Undernourished Individuals? - Larissa Lumi Watanabe Ishikawa; Larissa Camargo da Rosa; Thais Graziela Donegá França; Raphael Sanches Peres; Fernanda Chiuso-Minicucci; Sofia Fernanda Gonçalves Zorzella-Pezavento; Alexandrina Sartori (Clinical and Developmental Immunology)
Cellular immunity is critical for protection against tuberculosis, but its integrity is compromised during undernutrition. The present study was designed to evaluate if the attenuated mycobacterium BCG is a safe vaccine for undernourished individuals. An experimental model of undernutrition was established by subjecting BALB/c mice to dietary restriction. These animals received 70% of the amount of food consumed by the healthy control group and exhibited physiological alterations compatible with malnutrition, including body weight loss, reduced levels of triglycerides and glucose, and reduced lymphocyte numbers. Undernourished mice were immunized with BCG, and the mycobacterial loads in lymph nodes, spleen, liver, lungs, and thymus were determined. A much higher proportion of undernourished mice exhibited bacterial dissemination to the lymph nodes, spleen and liver. In addition, only undernourished animals had bacteria in the lungs and thymus. Concomitant with higher mycobacterial loads and more widespread BCG dissemination in undernourished mice, production of TNF-α, IFN-γ, and IL-10 was also diminished in these mice. Taken together, these results indicate that BCG infection is more severe in undernourished mice. Whether a similar phenomenon exists in undernourished children or not remains to be thoroughly investigated.